PREVALENSI VIRAL NERVOUS NECROSIS (VNN) PADA IKAN KERAPU EKOR BULAN (Variola sp.) DI PERAIRAN GORONTALO: Prevalence of Viral Nervous Necrosis (VNN) in Lunar-Tailed Grouper (Variola sp.) in Gorontalo Waters - Nurkhozin, Ahmad Ainul; Achmad, Dewi Shinta; Bakti, Nurqadri Syaia; Yasin, Indri Afriani; Natsir, Sitti Rosnany Alwi (Program Studi Teknologi Hasil Perikanan|Fakultas Pertanian|Universitas PGRI Banyuwangi, 2022)
Grouper (Family Serranidae) is one of the betanodavirus hosts. Betanodaviruses can infect species in tropical, subtropical or cold climates. This is a major concern because it has been reported to infect a variety of marine fish, both farmed and wild fish. The disease caused by this virus is commonly known as Viral Nervous Necrosis (VNN) or Viral Encephalopathy and Retinopathy (VER). This VNN disease is characterized by vacuolar necrosis of cells found in the brain, retina and spinal cord, can cause up to 100% mortality in larvae and juveniles and can cause significant losses in older fish. Infected fish, both wild and farmed, can act as reservoirs (nesting sites and breeding grounds for viruses) and can be a source of infection for farmed species. The method used in this study was descriptive method, while the Lunar-Tailed grouper (Variola sp.) samples used in this study were groupers caught measuring 26-42 cm. VNN testing on groupers by taking target organs (brains and eyes) then fixing them in 95% Ethanol then PCR testing at the Virology Laboratory. The results of this study indicate a different prevalence in the two waters in Gorontalo.